2015 International Conference on Affective Computing and Intelligent Interaction (ACII) 2015
DOI: 10.1109/acii.2015.7344554
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning vs. kernel methods: Performance for emotion prediction in videos

Abstract: Recently, mainly due to the advances of deep learning, the performances in scene and object recognition have been progressing intensively. On the other hand, more subjective recognition tasks, such as emotion prediction, stagnate at moderate levels. In such context, is it possible to make affective computational models benefit from the breakthroughs in deep learning? This paper proposes to introduce the strength of deep learning in the context of emotion prediction in videos. The two main contributions are as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 21 publications
0
56
0
Order By: Relevance
“…Different approaches are proposed in the literature to computationally infer emotional information from a film. The approach proposed by [22], based on convolutional neural networks, enables to calculate dimensional affective scores for 1-second video portions, on the arousal and valence dimensions (the model is described in details in [23]). Another approach was proposed by Soleymani et al [24], based on a Bayesian classification framework, to classify film scenes into three affective categories: 'calm', 'positive excited', or 'negative excited'.…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches are proposed in the literature to computationally infer emotional information from a film. The approach proposed by [22], based on convolutional neural networks, enables to calculate dimensional affective scores for 1-second video portions, on the arousal and valence dimensions (the model is described in details in [23]). Another approach was proposed by Soleymani et al [24], based on a Bayesian classification framework, to classify film scenes into three affective categories: 'calm', 'positive excited', or 'negative excited'.…”
Section: Discussionmentioning
confidence: 99%
“…Here we focus on the continuous subset of the LIRIS-ACCEDE database, which contains 30 full movies, totalling 442 minutes [20]. During data collection, 10 participants watched each movie once and annotated continuous arousal and valence scores (value range [-1,1]) of the emotions they felt during watching (movie induced emotions).…”
Section: Previous Work On Liris-accede Databasementioning
confidence: 99%
“…[28] and [29]). In fact, Baveye et al [20] built a SVR model using only visual features and achieved best reported CC for this task. However, combining multimodal information has improved performance for a number of other emotion recognition tasks (e.g.…”
Section: Previous Work On Liris-accede Databasementioning
confidence: 99%
See 1 more Smart Citation
“…Logistic regression is then used to predict sentiments using the generated mid-level representations. More recently, Baveye et al [4] compared CNNs applied on video keyframes against the combination of Support Vector Regression (SVR) and low-level features, and reached the conclusion that CNNs constitute a promising solution. Xu et al [40] perform emotion recognition in videos using a BoW approach, where the dictionary is constructed by clustering features obtained from so-called auxiliary images by means of CNNs.…”
Section: From a Feature Representation Point Of Viewmentioning
confidence: 99%